Real space dynamics of attractive and repulsive polarons in Bose-Einstein condensates - Drescher, Moritz; Salmhofer, Manfred; Enss, Tilman (Arxiv, 2018)
We investigate the formation of a Bose polaron when a single impurity in a Bose-Einstein condensate is quenched from a non-interacting to an attractively interacting state in the vicinity of a Feshbach resonance. We use a beyond-Fr\"ohlich Hamiltonian that is able to cover both sides of the resonance and the Lee-Low-Pines variational ansatz to compute the time-evolution of Boson density profiles in position space. We find that on the repulsive side of the Feshbach resonance, the system keeps oscillating with a characteristic frequency for which we derive an implicit equation and discuss to what extent this can be interpreted as a competition between a molecular and a repulsive polaron state. If the impurity is introduced at finite velocity, it is periodically slowed down or even arrested before speeding up again.
Identifizierung der Ressource nach: Last revised 1 Feb 2019
Gesehen am 08.12.2020